THE IMPORTANCE OF ULTRASONOGRAPHY IN THE DIAGNOSIS AND TREATMENT OF MUSCULOSKELETAL PROBLEMS OF HAEMOPHILIA A - Adriana Diaconu; Oana Rizea; Horatiu Vultur (Amaltea Medical Publishing House, 2018)
Haemophilia A, defined by a deficiency of clotting factor VIII, can cause bleeding in various locations, especially on muscles and joints. For these patients, ultrasonography plays a very important role in the monitoring and shaping of the replacement treatment with factor VIII, by confirming the time when full clinical-imaging complete remission is obtained.